Discovering anti-osteoporosis constituents of maca (Lepidium meyenii) by combined virtual screening and activity verification. (November 2015) - Liu, Hao; Jin, Wenwen; Fu, Chunhua; Dai, Penfei; Yu, Yuantao; Huo, Qin; Yu, Longjiang
Abstract: Maca ( Lepidium meyenii Walp.) is a traditional medicine and nutritional supplement from South America with many pharmacological effects, such as enhancing female and male fertility, improving sexual dysfunction, preventing osteoporosis and relieving menopausal syndrome. Until now, the active principles behind most of these effects have not been clarified, severely hindering the exploitation and application of maca products. In this study, the effective anti-osteoporotic components of maca are uncovered. Through virtual screening against estrogen receptor and verification of pharmacological activity on osteoblasts, we found that N-benzyl-palmitamide is an active constituent of maca in preventing osteoporosis. As well, N-benzyl-palmitamide promotes osteoblast proliferation, differentiation and mineralization, plus it benefits bone formation through enhanced expression of osteogenesis-related genes, such as bone morphogenetic protein-2, core binding factor alpha 1, type 1 collagen and alkaline phosphatase. The effects of N-benzyl-palmitamide on enhanced bone formation are very likely through the estrogen receptor pathway, as N-benzyl-palmitamide also increases the expression of ERα and ERβ genes. Clarifying single-component biological activity will greatly enable exploitation and application of maca as a medication and health supplement to prevent osteoporosis. Highlights: We screen out active constituent of maca in preventing osteoporosis by using virtual screening. N-benzyl-palmitamide is active constituent and its activity has been verified on osteoblasts. The effects of N-benzyl-palmitamide on enhanced bone formation are very likely through the estrogen receptor pathway.